Goat milk as a non-invasive sample for confirmation of Mycobacterium avium subspecies paratuberculosis by IS900 PCR - Sukumar, Bharathy; Gunaseelan, Lakshmanasami; Porteen, Kannan; Prabu, Karuppanasamy (Journal of Advanced Veterinary and Animal Research, 2014)
Mycobacterium avium subsp. paratuberculosis (MAP) causes Johne's disease (JD) in cattle, sheep, goats and other ruminants, and Crohns disease in humans. MAPs are shed to external environment through feces and milk. The present study was aimed to evaluate the utility of milk as a non-invasive sample in stage II MAP infections in goats using IS900 polymerase chain reaction (PCR) and sequencing analysis. A total of 32 milk samples from lactating does were collected. Within these 32 milk samples, 15 were collected from pre-confirmed JD positive goats. By IS900 PCR, all the 15 (100%) known JD positive goat milk samples revealed the presence of MAP. However, no unknown goat was identified as MAP positive. The results of this study established the usefulness of milk as a non-invasive sample in screening and confirmation of stage II MAP infection in goats. DOI: http://dx.doi.org/10.5455/javar.2014.a25 J. Adv. Vet. Anim. Res., 1(3): 136-139, September 2014